Quantitative susceptibility mapping versus phase imaging to identify multiple sclerosis iron rim lesions with demyelination - Huang, Weiyuan; Sweeney, Elizabeth M.; Kaunzner, Ulrike W.; Wang, Yi; Gauthier, Susan A.; Nguyen, Thanh D. (Journal of neuroimaging, 2022)
Background and Purpose To compare quantitative susceptibility mapping (QSM) and high‐pass‐filtered (HPF) phase imaging for (1) identifying chronic active rim lesions with more myelin damage and (2) distinguishing patients with increased clinical disability in multiple sclerosis. Methods Eighty patients were scanned with QSM for paramagnetic rim detection and Fast Acquisition with Spiral Trajectory and T2prep for myelin water fraction (MWF). Chronic lesions were classified based on the presence/absence of rim on HPF and QSM images. A lesion‐level linear mixed‐effects model with MWF as the outcome was used to compare myelin damage among the lesion groups. A multiple patient‐level linear regression model was fit to establish the association between Expanded Disease Status Scale (EDSS) and the log of the number of rim lesions. Results Of 2062 lesions, 188 (9.1%) were HPF rim+/QSM rim+, 203 (9.8%) were HPF rim+/QSM rim–, and the remainder had no rim. In the linear mixed‐effects model, HPF rim+/QSM rim+ lesions had significantly lower MWF than both HPF rim+/QSM rim– (p < .001) and HPF rim–/QSM rim– (p < .001) lesions, while the MWF difference between HPF rim+/QSM rim– and HPF rim–/QSM rim– lesions was not statistically significant (p = .130). Holding all other factors constant, the log number of QSM rim+ lesion was associated with EDSS increase (p = .044). The association between the log number of HPF rim+ lesions and EDSS was not statistically significant (p = .206). Conclusions QSM identifies paramagnetic rim lesions that on average have more myelin damage and stronger association with clinical disability than those detected by phase imaging.